Legionella bacteria in shower aerosols increase the risk of Pontiac fever among older people in retirement homes. Issue 10 (12th September 2008) - Bauer, M; Mathieu, L; Deloge-Abarkan, M; Remen, T; Tossa, P; Hartemann, P; Zmirou-Navier, D
Abstract : Background: 828 elderly subjects residing in nursing homes were followed up during 4 months to ascertain incidence of symptoms associated with Pontiac fever (PF) in a non-epidemic setting. Methods: The exposure situation was inhalation of Legionella bacteria while showering. An audit of the hot water system in all institutions allowed ascribing each subject to a water quality area wherefrom one shower was sampled for Legionella assays at the end of the follow-up period. Legionella were detected in water and aerosols using the culture (CFU, colony forming units) and in situ hybridization (FISH) techniques. Results: Among 32 Pontiac-like episodes, 29 cases complied with the operational definition of PF elaborated for this study. Incidence density was 0.11 case/person–year (95% CI 0.07 to 0.15). Water concentrations greater than 105 Legionella FISH/l and 104 Legionella CFU/l were associated with an increased risk of PF (respectively RR 2.23, p = 0.05 and RR 2.39, p = 0.11, with significant dose–response patterns: p for trend <0.04). The condition also seems associated with aerosol concentrations above 103 Legionella FISH/l of air. A significantly higher risk of Pontiac-like episodes (RR 6.24, 95% CI 2.12 to 18.38) was seen for elderly subjects receiving corticosteroid therapy. Conclusion: The water and threshold values identified in this research could be used to inform guidance measures aimed at protecting institutionalised older people from Legionnaires' disease. Immunosuppressive therapy in the same population group can significantly enhance susceptibility to Legionella bacteria.